2021
DOI: 10.1177/00469580211060184
|View full text |Cite
|
Sign up to set email alerts
|

SARS-COV-2 Vaccines: What Indicators are Associated with the Worldwide Distribution of the First Doses

Abstract: The present study aimed to identify the factors associated with the distribution of the first doses of the COVID-19 vaccine. In this study, we used 9 variables: human development index (HDI), gross domestic product (GDP per capita), Gini index, population density, extreme poverty, life expectancy, COVID cases, COVID deaths, and reproduction rate. The time period was until February 1, 2021. The variable of interest was the sum of the days after the vaccine arrived in the countries. Pearson’s correlation coeffic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 20 publications
1
6
0
Order By: Relevance
“…Intriguingly, the Gini index, which is an indicator measuring the degree of inequality in the income/wealth distribution and is computed as the proportion of the total income/wealth of the population cumulatively earned by the bottom percentage (x) of the population, was not found to be associated with the VRI. Even though surprising, this finding is in line with other studies, including the investigation by Sobral and colleagues [59].…”
Section: Discussionsupporting
confidence: 91%
“…Intriguingly, the Gini index, which is an indicator measuring the degree of inequality in the income/wealth distribution and is computed as the proportion of the total income/wealth of the population cumulatively earned by the bottom percentage (x) of the population, was not found to be associated with the VRI. Even though surprising, this finding is in line with other studies, including the investigation by Sobral and colleagues [59].…”
Section: Discussionsupporting
confidence: 91%
“…They have facilitated earlier access to vaccines and powered the required logistics of a large-scale vaccination campaign. Several studies signaled a positive association between coverage of COVID-19 vaccination, the Human Development Index (HDI), and gross domestic product (GDP) per capita 12 , 13 , 14 . Education and GDP per capita also contribute to the speed of the COVID-19 vaccination campaign 15 .…”
Section: Introductionmentioning
confidence: 99%
“…The impact of GDP was consistent with previous studies. 6 , 8 It is well-known that countries with higher GDP may have more sources of vaccines and well-developed mechanisms to promote vaccination. 21 The same phenomenon can been seen in the 2019-H1N1 influenza outbreak that developing countries identified the lack of equity in how developed countries were securing access to the vaccine 22 .…”
Section: Discussionmentioning
confidence: 99%
“… 7 One ecological study showed that the Gini index may be a negative factor for vaccination. 8 Education is often regarded as a macro-determinant of national population health and behavior. People in the countries with longer years of schooling have more access to enhance health literacy, which may affect the vaccination progress.…”
Section: Introductionmentioning
confidence: 99%